2010
DOI: 10.1002/app.32016
|View full text |Cite
|
Sign up to set email alerts
|

Spinning and characterizations of polypropylene/alkylphosphonic acid treated montmorillonite nanocomposite fiber

Abstract: Fine and well-dispersed clay was prepared via the in situ conversion of the dodecylamine intercalant inside the clay gallery to dodecylamino dimethylene diphosphonic acid (DDD), using a Mannich reaction, so as to create a repulsive force that delaminated the clay platelets. The clay structure and morphology were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), and Transmission electron microscopy (TEM) analysis, which revealed changes in the multilayer stacks. XRD analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, polymer composites which contain nanosized particles at a much lower loading ratio than conventional fillers have recently attracted a great deal of attention because they offer enhanced mechanical and thermal properties when compared to the conventional composites. Nano-sized particles, and particularly carbon nanotubes (CNTs) 6,7 and montmorillonite (MMNT) 8,9 particles, have taken the lead as the novel nanofillers for plastics, as well as for fibers, thanks to their high aspect ratio. Even though fillers with a high aspect ratio are ideal for plastic reinforcement, recently silica has been widely investigated for use in polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, polymer composites which contain nanosized particles at a much lower loading ratio than conventional fillers have recently attracted a great deal of attention because they offer enhanced mechanical and thermal properties when compared to the conventional composites. Nano-sized particles, and particularly carbon nanotubes (CNTs) 6,7 and montmorillonite (MMNT) 8,9 particles, have taken the lead as the novel nanofillers for plastics, as well as for fibers, thanks to their high aspect ratio. Even though fillers with a high aspect ratio are ideal for plastic reinforcement, recently silica has been widely investigated for use in polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is not common, but some reports also observed an increase of ε B with the addition of low amount of clay, especially organically modified montmorillonite. [41][42][43] Bakhtiar et al 44 and Dias et al 18 also reported a slight increase of ε B with the addition of small amount of mica in epoxy matrix and ultrahigh-molar mass polyethylene (UHMMPE), respectively. The improvement of toughness and impact strength with the addition of small amount of clay has also been reported by other authors, and can be attributed to a good dispersion of the filler inside the polymeric matrix.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…Recently, polymer nanocomposites which contain nano-sized particles at a much lower loading ratio than conventional fillers have been focused, they offer enhanced mechanical properties and thermal properties when compared to conventional composites. Nano-sized particles, particularly, carbon nanotube (CNT) [6][7] and montmorillonite (MMNT) [8][9] have taken a lead as the novel nano-fillers for plastics as well as fibers due to their high aspect ratio. Recently silica has been widely investigated for polymeric materials and held a great potential for developing nanocomposites.…”
Section: Introductionmentioning
confidence: 99%